Prevalence and clinical significance of iron deficiency in patients with acute decompensated heart failure - E. A. Smirnova; E. V. Sedykh; S. S. Yakushin; S. V. Subbotin (Российский кардиологический журнал)
Aim. To study the prevalence of iron deficiency (ID) and anemia, as well as their impact on the clinical performance and quality of life in patients with acute decompensated heart failure (ADHF).Material and methods. The work was performed as part of cross-sectional multicenter screening study of ID in patients with heart failure (HF), managed by the Russian Society of Heart Failure. We examined 80 patients hospitalized in the cardiology department due to ADHF, who signed an informed consent. The diagnosis of ADHF was based on clinical signs of decompensated heart failure requiring intravenous therapy with diuretics, vasodilators, or inotropic agents.Results. The prevalence of ID was 80,0%, anemia — 35,0%, combination of anemia and ID — 31,2%. The mean age of patients with ID was 69,4±10,9 years. Patients with ID had higher HF class (40,6% vs 6,3% without ID, p<0,001), a higher incidence of hydrothorax (65,6% vs 31,3%, p=0,012), higher N-terminal pro-brain natriuretic peptide (5155,5 [3267,3;9786,3] pg/mL vs 2055,5 [708,8;2839,0] pg/mL, p<0,001), lower 6-minute walk test distance (155,9±84,0 m vs 239,6±82,7 m in patients without ID, p=0,01), lower quality of life according to the visual analogue scale (36,4±16,3 vs 46,3±20,7, p=0,036). ID was more often recorded in patients with frailty (95,7% vs 73,7% in patients without frailty, p=0,003), requiring a higher starting dose of intravenous diuretics (50,9±18,9 mg vs 38,6±12,3 mg without ID, p=0,021).Conclusion. In patients hospitalized due to ADHF, the prevalence of ID is 80,0%, anemia — 35,0%, combination of ID and anemia — 31,2%. Patients with ID have a higher N-terminal pro-brain natriuretic peptide level, more severe signs of decompensation, which requires higher starting dose of loop diuretics. Patients with ID are more likely to have frailty, lower exercise tolerance and quality of life.